2009
DOI: 10.1021/jp906651n
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Sulfur Species: Kinetics and Mechanism of the Oxidation of Aryl Sulfinates with Hypochlorous Acid

Abstract: The mechanism of oxidation of ArSO(2)(-) (PhSO(2)(-) and 5-sulfinato-2-nitrobenzoic acid = TNBO(2)(1-/2-)) with HOCl/OCl(-) has been investigated using the kinetic method. In contrast to previous reports for PhSO(2)(-) (for which it was suggested that OCl(-) and not HOCl was the reactant), the reaction proceeds through a conventional pathway: nucleophilic attack by ArSO(2)(-) on HOCl with concomitant Cl(+) transfer to give a sulfonyl chloride intermediate (ArSO(2)Cl), which we have identified spectrophotometri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…NMR titration results, also affording effective K d values, corroborated the crystal data by characteristic 19 F chemical shifts and through hydrogen/deuterium primary isotope shifts. The magnitude of the isotope shifts and quantitation of 1 H- 19 F NOEs afforded solution structure measurements. These results suggest that a pentacoordinate phosphorane is not appropriate to describe the transition structure.…”
Section: Transfer At Phosphorussupporting
confidence: 68%
See 2 more Smart Citations
“…NMR titration results, also affording effective K d values, corroborated the crystal data by characteristic 19 F chemical shifts and through hydrogen/deuterium primary isotope shifts. The magnitude of the isotope shifts and quantitation of 1 H- 19 F NOEs afforded solution structure measurements. These results suggest that a pentacoordinate phosphorane is not appropriate to describe the transition structure.…”
Section: Transfer At Phosphorussupporting
confidence: 68%
“…À derivatives by HOCl/OCl À is normally expected to proceed through nucleophilic attack of ArSO 2 À on HOCl, with concomitant transfer of Cl + , however an alternative mechanism with OCl À nucleophilic attack on ArSO 2 À , to form a sulfurane intermediate (ArSO 2 Cl 2À ) has recently been proposed and tested. 19 These reactions were followed by UV-vis spectroscopy, and products also were confirmed by 1 H NMR spectroscopy and HPLC analysis, with ArSO 2 Cl, not a sulfurane, identified as an intermediate. The rate of hydrolysis of ArSO 2 Cl was studied between pH 0 and 13.7 and afforded pseudo-first order kinetics with ArSO 3 À identified as the product.…”
Section: Oxidation Of Arsomentioning
confidence: 88%
See 1 more Smart Citation
“…Step R5 is a competitive process with step R4 that leads to the formation of S 2 O 3 I − instead of hypoiodous acid and S 2 O 3 OH − . This process is a formal electrophilic I + transfer frequently occurring in different oxidation reactions of hypohalogenous acids. , It may seem surprising that hypoiodous acid can react with thiosulfate via an oxygen transfer (step R4) and a I + transfer (step R5) pathway simultaneously as well, but this result is not a unique feature of the kinetic behavior of hypohalogenous acid. Fogelman et al have already reported that hypochlorous acid reacts with sulfite via parallel oxygen transfer and Cl + transfer to produce sulfate and chloride eventually.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore rather amazing—and in many ways very fortunate—that the field of inorganic RSS over the years has developed its own dynamic, fuelled by three parallel developments: (a) the stream of ten prominent publications on inorganic RSS by Michael Ashby and his colleagues between 2004 and 2010, all with a title commencing with “Reactive Sulfur Species” and focussed on inorganic RSS [46,72,73,74,75,76,77,78,79,80,81], (b) The eruption of H 2 S research, accompanied by the suspicion that H 2 S is probably not really the signalling molecule one had previously thought, but that there is a case of mistaken identity, involving an entire series of inorganic polysulfides (H 2 S x ), which clearly belong to the realm of inorganic RSS, (c) the issue of the lost electron, i.e., the rather curious situation that many interactions involving thiols and radicals, for instance in the field of S-nitrosothiols, do not add up when it comes to electrons, hence questioning if RSS are really predominantly electrophilic compounds, such as sulfenic acids, or rather radical species. We will now consider the inorganic side of sulfide species in more detail.…”
Section: What Are Rss?mentioning
confidence: 99%